Pertumbuhan Benih Ikan Nila (Oreochromis niloticus) Yang Diberi Pakan Fermentasi Berbasis Air Kelapa - Markhamah, Markhamah; Djauhari, Ricky; Yasin, Muhamad Noor (Jurnal Perikanan Unram, 2025)
Research on fermented feed based on green coconut water combined with molasses and EM4 in the maintenance of tilapia (Oreochromis niloticus) fry in flooded soil ponds has not been conducted until now. Therefore, research using fermented feed needs to be conducted to obtain the right usage technique. This study aims to determine the effective dose of coconut water to improve the growth performance of tilapia fry maintained in soil ponds. This study used a completely randomized design (CRD) with four treatments and three replications. The treatments given in this study consisted of treatment A (Treatment without giving green coconut water, commercial pellet feed 1 kg + 200 mL boiled water + 20 mL molasses + 10 mL EM4 probiotic), B (Treatment commercial pellet feed 1 kg + 150 mL boiled water + 50 mL  coconut water + 20 mL molasses + 10 mL EM4 probiotic), C (Treatment commercial pellet feed 1 kg + 100 mL boiled water + 100 mL coconut water + 20 mL molasses + 10 mL EM4 probiotic), and D (Treatment commercial pellet feed 1 kg + 200 mL coconut water + 20 mL molasses + 10 mL EM4 probiotic). Tilapia seeds measuring 2.66-3.06 g were randomly spread into 12 hapa nets measuring 1x1x1 m3, which were installed in an earthen pond with a stocking number of 30 fish/hapa net. The test fish were kept for 28 days and given test feed with a frequency of 1 time/day. The research parameters consisted of harvest biomass (Bt), daily growth rate (DGR), feed conversion ratio (FCR), feed efficiency (EP), and survival rate (SVR). Providing fermented feed based on green coconut water with the lowest and highest doses did not provide optimum results on the growth of catfish. Optimum results were obtained in treatment B.